(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Conflict is defined as a conflict that occurs in a humanitarian relationship (intrapersonal orinterpersonal) between one party and another in achieving a goal, conflict will arise due to differences ininterests, emotions or psychology and values. Role conflict happens when employees are given multiple,incompatible roles at once or when their role overlaps with that of another employee or work group. Aworker is more likely to experience stress at work if there is more role conflict.Aims-To assess the socioeconomicprofile of the working women and the factors of role conflict between family and workplace.Methods-The data for the present study have been collected by using the observation and interviewschedule technique from 100 respondents for the fulfillment of the information. Purposive sampling wasused to select the working women in private sectors.Result-The majority of respondents are 31-40 yrs.age group, female, Hindu, married and degreediploma holder. Work-family conflict is high degree forworking women in private sector. Role conflict generating factors are heavy work load, negative attitudesof senior, financial problems unfavourable attitude of husband, failures in children care and multipleroles.